Effects of forewarnings on children's and adults' spontaneous false memories. Issue 2 (4th March 2022) - Schopen, Katharina; Otgaar, Henry; Howe, Mark L; Muris, Peter
ABSTRACT: The current experiment examined the effect of forewarning on children's (11 to 12 years of age) and adults' spontaneous false memory creation by presenting participants with semantically related word lists that are often used to elicit false memories (i.e., Deese-Roediger-McDermott (DRM) paradigm). The forewarning consisted of an explanation of the false memory effect and a demonstration of a DRM word list and an associated recognition task. It was hypothesized that children would have fewer false memories than adults using the DRM paradigm and that forewarning would reduce the number of critical lures remembered by children and adults. We found a developmental reversal effect in that children had lower false memory levels than adults and that forewarning reduced, but did not eliminate, false memory propensity in both children and adults. Our findings further indicated that forewarning was more effective in reducing false memory levels in 11- to 12-year-old children than in adults. Finally, analyses revealed that participants were more accurate when they received a forewarning as compared to when they did not.